PENILAIAN KINERJA PENYULUH DI KESATUAN PENGELOLAAN HUTAN (KPH) BARITO TENGAH KABUPATEN BARITO UTARA KALIMANTAN TENGAH - Rika Septiari; Asysyifa Asysyifa; Arfa Agustina Rezekiah (Universitas Lambung Mangkurat, 2024)
The Central Barito forest management unit (FMU) is located in North Barito Regency, Central Kalimantan, and its working area covers 7 (seven) sub-districts. The Central Barito FMU has experienced a decline in its carrying capacity either due to natural forces or human intervention. This requires the role of forestry extension workers to empower the community, therefore this research was conducted to analyze the performance of forestry extension officers. Data collection in this study was carried out by direct interviews with respondents. The results of interview data with forestry extension officers at KPH Barito Tengah, North Barito Regency, Central Kalimantan Province were analyzed according to the criteria for assessing forestry extension officers, Minister of Forestry Regulation Number P.43/MENLHK/SETJEN/KUM.1/5/2016 concerning General Guidelines for the Implementation and Appreciation of Sustainable Ecosystems. Based on the assessment of the 7 criteria or indicators for assessing forestry extension agents, the average value of the performance of forestry extension officers at KPH Barito Tengah is in the good category with a score of 77.99.Kesatuan pengelolaan hutan (KPH) Barito Tengah berada di Kabupaten Barito Utara Kalimantan Tengah. KPH Barito Tengah berada di wilayah kerja 7 (tujuh) kecamatan. KPH Unit Barito Tengah telah mengalami penurunan daya dukungnya baik disebabkan oleh sumber alam itu sendiri ataupun karena adanya campur tangan manusia dari hal tersebut sangat diperlukan peran penyuluh kehutanan untuk memberdayakan masyarakat, oleh karena itu penelitian ini dilakukan untuk menganalisis kinerja penyuluh kehutanan. Metode pengambilan data pada penelitian ini dengan cara metode wawancara langsung kepada responden. Hasil data wawancara terhadap penyuluh kehutanan di KPH Barito Tengah Kabupaten Barito Utara Provinsi Kalimantan Tengah dianalisis sesuai kriteria Penilaian penyuluh kehutanan Peraturan Menteri Kehutanan Nomor P.43/MENLHK/SETJEN/KUM.1/5/2016 tentang Pedomanan Umum Untuk Penyelenggaraan dan Apresiasi Wana Lestari. Berdasarkan penilaian dari 7 kriteria atau indikator penilaian penyuluh kehutanan nilai rata-rata kinerja penyuluh kehutanan di KPH Barito Tengah ternasuk dalam kategori bagus dengan skor sebesar 77,99.